2017
DOI: 10.1080/10538720.2017.1310644
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies used by LGB older adults in facing and anticipating health challenges: A narrative analysis

Abstract: Given that lesbian, gay, and bisexual (LGB) older adults face notable health disparities compared to their heterosexual counterparts, there is a need for understanding how LGB adults cope with health challenges in late life. The current study analyzes narratives from nine LGB adults age 65 and older living in an urban area in the Southeast U.S. Participants spoke of coping strategies related to health promotion behaviors, shifting perspectives of health and body, trusting in spirituality for comfort, and accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 43 publications
0
16
1
Order By: Relevance
“…We found that in 25% of these articles, authors used theory or a concept for the purpose of conceptual development or expansion. For example, one article used the concept of coping to motivate and frame a study but also applied the analysis and findings to expand this concept and offer a more nuanced understanding of its meaning and function in the lives of LGB older adults (Seelman, Lewinson, Engelman, Maley, & Allen, 2017). Another used the convoy model of social relations to motivate and design a study of social networks of older gay men and used the empirical material to add substantive and conceptual dimensions to this well-known model in gerontology (Tester & Wright, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that in 25% of these articles, authors used theory or a concept for the purpose of conceptual development or expansion. For example, one article used the concept of coping to motivate and frame a study but also applied the analysis and findings to expand this concept and offer a more nuanced understanding of its meaning and function in the lives of LGB older adults (Seelman, Lewinson, Engelman, Maley, & Allen, 2017). Another used the convoy model of social relations to motivate and design a study of social networks of older gay men and used the empirical material to add substantive and conceptual dimensions to this well-known model in gerontology (Tester & Wright, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Second, we noted that some articles stemmed from social or nonbiomedical sciences and focused especially on describing and explaining how social and psychological phenomena and processes occur or unfold, using theories and concepts such as the convoy model of social relations (Kim, Fredriksen-Goldsen, Bryan, & Muraco, 2017; Tester & Wright, 2017), communal relationship theory (Muraco & Fredriksen-Goldsen, 2014), social integration theory (Williams & Fredrisksen-Goldsen, 2014), social capital theory (Erosheva, Kim, Emlet, & Fredriksen-Goldsen, 2015), the sailing model of estrangement (deGuzman et al, 2017), defensive othering (Suen, 2017), the individualization thesis (Almack et al, 2010), a framework explaining long-term care strategies of older lesbians (Gabrielson, 2011), sexual fluidity (Averett et al, 2011), normative creativity (Parslow & Hegarty, 2013), aging capital (Simpson, 2013), successful aging (Fredriksen-Goldsen, Kim, Shiu, Goldsen, & Emlet, 2014; Porter, Ronneberg, & Witten, 2013; Van Wagenen, Driskell, & Bradford, 2013), subjective well-being (Sagie, 2015), internalized ageism (Wight, LeBlanc, Meyer, & Harig, 2015), agency in the life course (Fabbre, 2017), coping and coping strategies (Seelman et al, 2017), perceived control (Hostetler, 2012), the Andersen Model (Brennan-Ing, Seidel, London, Cahill, & Karpiak, 2014), Ryff and Singer’s conceptualization of psychological well-being (Putney, 2014), socioemotional selectivity theory (Sullivan, 2014), social practice theory (SPT; Cohen & Cribbs, 2017), and internalized and enacted sexual identity stigma (Emlet, Fredriksen-Goldsen, Kim, & Hoy-Ellis, 2017). While examining different processes, these approaches “dig deep” into the complex ways that social forces and psychological functioning inform identity and well-being.…”
Section: Resultsmentioning
confidence: 99%
“…We adopted a narrative analysis approach in this study to better understand the entertainment content in 13 Reasons Why Season 1. Narrative analysis is an analytic approach in social and behavioral sciences with a focus on the interpretation of information conveyed in the form of stories, and it has been used in social psychology, communication research, and media studies [ 65 , 66 ]. Scholars have examined a wide range of elements from character development and overarching themes to narrative structure and dramatic performance, but these choices are usually made according to the study aims and research inquiries [ 65 ].…”
Section: Methodsmentioning
confidence: 99%
“…These older individuals have a higher tolerance to ART, as they cite fewer reasons to switch treatment, such as nausea or need for a simpler regimen [28]. Furthermore, among HIV-positive LGBT adults, aging may promote selfacceptance and a will to live that enhances adherence to medications [29,30].…”
Section: Secondary Findingsmentioning
confidence: 99%